The Impact of Tourism Industry Development In Relation to Violations of Utilisation of Cliff Borders by Tourism Entrepreneurs - Luh Putu Suryani; Ida Ayu Putu Widiati; Indah Permatasari (Sociological Jurisprudence Journal, 2022)
It is undeniable that the development of the tourism industry can have both positive and negative impacts on the economic, socio-cultural and environmental sectors. In the context of Bali, development of tourism industry will certainly have impacts towards the development of tourism supporting facilities in the form of hotels, restaurants, entertainment and recreation and so on. The aims of this research are to examine the impacts of the development of the tourism industry in relation to violations of the utilisation of cliff borders by tourism entrepreneurs and the one that involves reconstruction of legal norms in accordance with the concept of sustainable tourism development. The research takes the type of empirical legal research. The results show that the existence of tourism supporting facilities on the cliff borders in turn brings about negative impacts on the environment. As a consequence, legal reconstruction is urgently needed by adding more detailed justifications related to the regulations regarding the cliff border areas. The legal reconstruction in question can be done by adding the provisions of Articles in Provincial and Regencial or Municipal Regulations, or can be executed through preparation or reconstruction of additional provisions of Articles in the Regencial or Municipal Spatial Detail Plan or through zoning regulations based on sustainable tourism development.